STRATEGY AND FORECASTING OF EFFECTIVE USE OF INVESTMENTS IN BUSINESS ACTIVITY - ISAKOV, AHMADALI (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
In the article, in the management of the process of formation of investment resources, it is necessary to determine the total volume of investment resources, to choose an effective method of financing investment activities, to ensure the maximum amount of investment resources attracted from internal and external sources, to form investment resources, to ensure the optimal amount of financing investment resources, to ensure the optimal ratio of capital to investment resources the issues related to ensuring the minimum value have been scientifically and theoretically studied and analyzed.